New-generation Indian Linear Accelerator: Validation of Specifications and Comparative Analysis - Ramamoorthy Ravichandran; Tarani Mondal; Tamilarasan Mani; Avinash Rao Kuppa; Madhu Govindappa; Manikandan Palanisamy; G. V. Subrahamanyam (Journal of Medical Physics)
Introduction: Radiotherapy (RT) plays a crucial role in cancer treatment, with two-thirds of patients receiving external-beam radiation therapy (EBRT). In India, the growing cancer burden necessitates a significant expansion of RT infrastructure. The current estimates indicate a severe shortfall, with only 0.6 RT machines per million people, far below international recommendations. To bridge this gap, India has focused on developing indigenous linear accelerators under the “Make in India” initiative. In the recent past, a low energy model linear accelerator is designed and manufactured in India and are being installed in different oncology centers. The performance specifications are reviewed and compared with well tested imported model to assess the efficacy in terms of radiation delivery parameters. Materials and Methods: A low-energy linear accelerator (6 MV), magnetron radiofrequency-powered model, Siddharth II©, is manufactured by M/s Panacea Medical Technologies Pvt Ltd., India, as an indigenous venture. This O-ring structure includes a Kilo-voltage imaging facility and tertiary multi-leaf collimators for image-guided intensity-modulated and volumetric arc radiation therapy. Measured data on the machine’s performance, beam characteristics, and radiation safety parameters during commissioning and type approval of five such linacs are summarized. In addition, an attempt has been made to compare the efficacy of this model with the measured 6 MV photon values of the imported TrueBeam© model from M/s Varian AG, USA. Results: The performance evaluation of five linear accelerators installed over the past 2 years, along with measured radiation data, confirms that the 6 MV linac has an adequate design, delivering radiation beams comparable to well-tested imported models widely used in India. Additionally, all radiation safety parameters of the Siddharth II© linac are on par with those of imported machines. Conclusion: The results demonstrate that the Siddharth II© linac meets clinical requirements and compares favorably with imported models. The successful implementation of this technology marks a significant step toward self-reliance in cancer treatment infrastructure, ensuring wider accessibility and affordability for Indian patients.